INDCOMP: A Shiny App for Open Data Repository of the Performance of an Indonesian Company Listed at the Indonesia Stock Exchange - Gio, Prana Ugiana; Mawengkang, Herman; Zarlis, Muhammad; Suwilo, Saib (Engineering, Technology & Applied Science Research, 2024)
Investors, practitioners, and stock researchers highly need data related to financial performance to predict a company’s financial health condition, which is used as a basis to consider investing in it. The Indonesia Stock Exchange (IDX) website provides reports on the company’s financial performance. Unfortunately, the company’s financial data found on the IDX website are in PDF format, and researchers must download them one by one, which takes a long time. This study presents a website-based application, named Indonesia Company Performance (INDCOMP), built using the R programming language and involving various R packages and frameworks to assist investors, practitioners, and stock researchers in studying the financial performance of companies. This application can help users quickly access the financial performance data of various companies, present financial performance data in data tables, and perform data visualizations as well as statistical analyses.